Laporan Kasus: Fraktur Tertutup Distal Humerus Sinistra - Dwi Prasetyo Wati; Alifia Rifki Rimanda (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Closed distal humerus fractures are injuries involving the distal portion of the humeral bone without disruption of the overlying skin, most commonly resulting from direct trauma such as the impact of a heavy object or blunt force to the elbow region. Although relatively uncommon in adults, this type of fracture presents considerable complexity due to its proximity to neurovascular structures and the elbow joint. Diagnosis is established through targeted anamnesis, comprehensive physical examination, and radiographic imaging in two standard projections to assess the location, fracture pattern, and degree of displacement. Additional modalities such as computed tomography (CT) may be indicated in cases of articular or comminuted fractures to enhance operative planning. Management depends on fracture stability, the extent of displacement, and the condition of surrounding soft tissues. In unstable or comminuted fractures, operative intervention such as Open Reduction and Internal Fixation (ORIF) is the preferred approach to restore bony continuity, reconstruct articular anatomy, and enable early mobilization. The primary therapeutic goals are to optimize elbow function, maintain joint stability, and prevent long-term complications including stiffness, malunion, delayed union, or non-union. Postoperative rehabilitation plays a crucial role in preventing restricted range of motion and restoring extremity strength. This case report describes a 49-year-old male with a comminuted closed distal humerus fracture of the left arm following direct trauma from a heavy object. The patient underwent complete clinical and radiological evaluation and was treated with ORIF. Early outcomes demonstrated adequate restoration of stability and alignment, affirming that accurate diagnostic assessment and timely intervention significantly contribute to optimal functional recovery of the affected extremity.